Hubungan Beban Kerja Mental dan Shift Kerja Terhadap Stres Kerja pada Pegawai Lotte Grosir Pakansari di Masa Pandemi Covid-19 Tahun 2021 - Khusnul Khotimah (2021)
Work stress is a condition of someone feelings related to work so that it affects emotions and thought processes. Employees who are still doing work more than two jobs at the same time, which can trigger mental workload. In addition, work shifts also have an important role in the work stress experienced by employees. The purpose of this study was to determine the relationship between mental workload and work shifts on work stress for Lotte Grosir Pakansari employees during the COVID-19 pandemic in 2021. This study was quantitative using a cross sectional study design with chi square test. The number of samples using total sampling obtained 56 employees of Lotte Grosir Pakansari. The research instrument used is Depression, Anxiety, Stress Scale 42 (DASS-42) sub-scale stress, and Rating Scale Mental Effort (RSME). The results of the analysis showed that there was a relationship between mental workload and work stress p-value = 0.000 (p > 0.05) and there was also a relationship between work shifts and work stress p-value = 0.021 (p > 0.05). Companies is expected to reduce the work load of employees or perform a clear division of tasks every day in order to avoid the mental workload experienced by employees. Keywords: Mental Workload, Shift Work, Work Stress